Physico-chemical composition and oxidative stability of South African beef, game, ostrich and pork droëwors - Descalzo, Adriana Maria; Mukumbo, Felicitas E.; Arnaud, Elodie; Collignan, Antoine; Hoffman, Louwrens C.; Muchenje, Voster (2019)
Droëwors are traditional South African salted and dried sausages, made without nitrites/nitrates and non- fermented. Different meat sources (beef, game and ostrich) are traditionally used in droëwors processing, while the use of pork is uncommon, as it is said to lead to rancidity. The first part of the study analysed the physico-chemical composition of commercially available beef, game and ostrich meat droëwors (n = 20). On average, they were composed of 26.3–29.2 g/100 g moisture, 41.3–44.0 g/100 g protein, 26.2–33.1 g/100 g fat and 5.9–6.5 g/100 g ash and 5.0–5.4 pH. Water activity (0.76–0.82) was sufficiently low to ensure shelf stability at ambient temperatures. In the second part beef and pork droëwors were formulated in accordance with these results and with similar fat content, dried for 2 days (30 °C, 40% relative humidity) and stored for 26 days (25 °C, 50% relative humidity); measuring moisture, water activity, pH and lipid oxidative stability (thiobarbituric acid reactive substances (TBARS)) weekly. At day 5, moisture and thus water activity of pork droëwors was slightly higher compared to beef ones and fat and ash content slightly lower (P ≤ 0.05) despite similar weight loss. Even with slightly less fat, TBARS in pork droëwors were significantly higher after drying and throughout storage (3.83 vs 0.99 mg MDA equivalents/kg dry matter at a maximum).